Ventriculostomy-related Cerebral Hemorrhages after Endovascular Aneurysm Treatment - Ross, Ian B. (AJNR Am J Neuroradiol, 2003)
BACKGROUND AND PURPOSE: Recent evidence suggests that endovascular treatment of acutely ruptured aneurysms is equivalent, if not superior, to surgical treatment. Not all patients who undergo endovascular treatment do well, however. We have identified ventriculostomy-related hemorrhage to be a potential source of morbidity and mortality. METHODS: Prospectively gathered data on patients (n = 51) admitted to a hospital for the endovascular treatment of acutely ruptured aneurysms during a 2.5-year period was analyzed. RESULTS: Twenty-four patients had drains inserted, and three suffered symptomatic ventriculostomy-related cerebral hemorrhages. Two of the three patients were being treated with heparin, one of whom also received clopidogrel, and the third was being treated with low molecular weight heparin at the time. The latter had a normal platelet count, prothrombin time, and activated partial thromboplastin time. All cerebral hemorrhages were deemed to have occurred as a result of drain manipulation. CONCLUSION: The risk of hemorrhage must be considered when using anticoagulation and antiplatelet therapy in patients requiring ventriculostomy. Interventionalists must not only work closely with neurosurgeons when it is anticipated that a ventriculostomy may be needed but also ensure that there is good communication with the neurosurgical team during the postprocedural period.